The effects of economic development on democratic institutions and repression in non-democratic regimes: theory and evidence - Alexander Kemnitz; Martin Roessler (Constitutional Political Economy, 2022)
This paper provides a theoretical rationale for the simultaneous use of repression and democratic institutions by a non-democratic government, as is often observed in reality. We find that economic development has different impacts on the levels of repression and democracy, depending on whether it appears in the form of rises in income or in education: A higher income level reduces democracy, whereas more education leads to both more democracy and more repression. These theoretical implications are corroborated by dynamic panel data regressions.
Keywords: C33; D72; K38; H11; O10; 330; Democracy; Repression; Non-democratic government; Economic development